2015
DOI: 10.1111/bjh.13591
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐transplant comorbidity burden and post‐transplant chronic graft‐versus‐host disease

Abstract: Summary The Hematopoietic Cell Transplantation-Comorbidity Index (HCT-CI) was designed as a predictor of non-relapse mortality after HCT. Chronic graft-versus-host disease (GVHD) contributes to mortality after HCT. Here, we investigated whether the HCT-CI could predict development of chronic GVHD or post-chronic GVHD mortality. We retrospectively analyzed data from 2,909 patients treated at four institutions with allogeneic HCT for malignant and non-malignant hematologic conditions. In Cox regression models ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Graft-versus-host disease was a common posttransplantation complication that could lead to significant morbidity and mortality after allogeneic HSCT. 33,34 It has been previously observed that GVHD could impair QOL in survivors of HSCT 35 and our study indicated that GVHD was related to more frequent PC use. Among decedents who underwent allogeneic HSCT, Hispanic populations were less likely to receive PC than Caucasian populations.…”
Section: Discussionsupporting
confidence: 57%
“…Graft-versus-host disease was a common posttransplantation complication that could lead to significant morbidity and mortality after allogeneic HSCT. 33,34 It has been previously observed that GVHD could impair QOL in survivors of HSCT 35 and our study indicated that GVHD was related to more frequent PC use. Among decedents who underwent allogeneic HSCT, Hispanic populations were less likely to receive PC than Caucasian populations.…”
Section: Discussionsupporting
confidence: 57%
“…Comorbidities present in HSCT recipients at the time of transplant are associated with decreased overall survival due to increased rates of nonrelapse mortality (NRM), including adverse outcomes associated with acute and chronic GVHD (42)(43)(44). Thus, GVHD prophylaxis strategies that minimize additional systemic toxicities in the early posttransplant period should provide clinical benefits by lowering NRM risks after aHSCT.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent report demonstrated that the incorporation of classic inflammatory biomarkers such as ferritin and albumin to the HCT-CI increased the performance of this index in predicting outcomes after allo-HCT [5]. Interestingly, the HCT-CI was not associated with the development of chronic GVHD [6], suggesting that the mechanisms by which comorbidities influence outcomes after allo-HCT are at least partially related to the pathophysiologic mechanisms of aGVHD.…”
Section: Introductionmentioning
confidence: 99%